Helicobacter pylori and gastroduodenal pathology: New threats of the old friend - Sechi Leonardo A; Ahmed Niyaz (BMC, 2005)
Abstract The human gastric pathogen Helicobacter pylori causes chronic gastritis, peptic ulcer disease, gastric carcinoma, and mucosa-associated lymphoid tissue (MALT) lymphoma. It infects over 50% of the worlds' population, however, only a small subset of infected people experience H. pylori-associated illnesses. Associations with disease-specific factors remain enigmatic years after the genome sequences were deciphered. Infection with strains of Helicobacter pylori that carry the cytotoxin-associated antigen A (cagA) gene is associated with gastric carcinoma. Recent studies revealed mechanisms through which the cagA protein triggers oncopathogenic activities. Other candidate genes such as some members of the so-called plasticity region cluster are also implicated to be associated with carcinoma of stomach. Study of the evolution of polymorphisms and sequence variation in H. pylori populations on a global basis has provided a window into the history of human population migration and co-evolution of this pathogen with its host. Possible symbiotic relationships were debated since the discovery of this pathogen. The debate has been further intensified as some studies have posed the possibility that H. pylori infection may be beneficial in some humans. This assumption is based on increased incidence of gastro-oesophageal reflux disease (GERD), Barrett's oesophagus and adenocarcinoma of the oesophagus following H. pylori eradication in some countries. The contribution of comparative genomics to our understanding of the genome organisation and diversity of H. pylori and its pathophysiological importance to human healthcare is exemplified in this review.